Acceptability of pre-exposure prophylaxis and associated factors among HIV-negative young men in Kagwara fishing community-Serere district, Uganda: A cross-sectional study - Alex Omoding; Ronald Opito; Paul Oboth; Francis Okello; Joseph K. B. Matovu (PLoS ONE, 2025)
Background Despite the potential efficacy of Pre-Exposure Prophylaxis (PrEP) in reducing HIV risk, Oral PrEP acceptability remains strikingly varied by populations and locations. We assessed PrEP acceptability and associated factors among at-risk HIV-negative young men. Methods A cross-sectional analytical study design was used. Data were collected among 409 at-risk HIV-negative young men aged 15–24 years living in Kagwara fishing community-Serere district, Uganda between August and October 2023. Quantitative data were collected on socio-demographic characteristics, sexual risk behaviors and concerns about PrEP. Data was analyzed using Stata version 15.0 statistical software. Summary statistics were computed and presented as tables, frequencies and proportions. Bivariate analysis was conducted using binary logistic regression to identify independent factors associated with PrEP acceptability. All factors that had p < 0.10 at the bivariate analysis and confounders were entered into the final logistic regression model. All factors with p < 0.05 were considered significantly associated with the primary outcome. Results The average age of 409 respondents was 21.8 (Standard Deviation [SD]=1.9) years. Majority, (97.8%, n = 393) had unprotected penetrative sex. PrEP acceptability was high as majority of the participants accepted to use PrEP based on the six constructs of acceptability (93.6%, n = 383). Participants with perceived risk of getting HIV infection had higher odds of PrEP acceptability, (adjusted odds ratio [aOR]=4.23, 95%CI = 1.05–17.04). Participants who knew their partner’s HIV status (aOR=0.25, 95%CI = 0.07–0.88), those who felt embarrassed to ask for PrEP from the facility (aOR=0.12, 95%CI = 0.04–0.39), and those who had stigma associated with use of PrEP (aOR=0.13, 95%CI = 0.04–0.41) had reduced odds of PrEP acceptability. Conclusion We found a high level of PrEP acceptability among young men at risk of HIV acquisition in Kagwara fishing community. Improving access to PrEP services among high risk young men in the fishing communities may increase PrEP uptake in this population and across similar settings. The Ministry of health needs to use multiple approaches to provide PrEP such as peer-led models, drug distribution points, short message reminders for refills, pharmacies and retail drug shops.